Fiber optic sensor for measurement of pressure - Shekh Muhammad Hafiz Shekh Raman (2015)
Fiber optics technology has been widely used and tremendously grown over the years. Measuring quantities such as pressures, temperature and other parameters can be utilized using the optical fiber as sensors. Its ability to provide distributed sensing over long distances which makes it feasible for this technology to be used in monitoring pipeline leakages. Gas leaks releases high pressure velocity thus producing acoustic energy and vibration along the pipeline by friction. The acoustic vibrations induce strain in optical fiber and thence cause a wavelength shift. Several optical approaches, particularly grating based sensors were explored and utilized to yield the optimum result in detecting pressure via optics. In this report, the fiber bragg grating based sensor is demonstrated for the acquiring and measurement of pressure which includes demonstrating static and dynamic strain. Several experimental set-ups such as the FBG interrogation system has been used to interrogate the strain induced Bragg wavelength shift. The Fibre Bragg Grating was bonded to a piezoelectric transducer for demonstrating dynamic measurements. This PZT acts as a simulation to an actual gas pipeline which will induce vibrations when voltage and frequencies is applied to it. Therefore several experimental set ups and data acquisition techniques are explored to obtain the output readings from the FBG. The PZT is subjected to 10 Hz to 1 MHz of input frequency to determine its range of effectiveness for FBG detection. In addition, the development of bonding techniques for accurate, robust and repeatable strain/pressure measurement on structure using fibre bragg grating is focused in this study.